The Effect of Square-Stepping Exercise on Balance of Elderly Adults at Risk of Falls - เสริมสินสิริ กัญชิตา; เสมศรี สุรีรัตน์; นนท์อัครวาทิน ศิรัสภรณ์ (Journal of The Royal Thai Army Nurses, 2019)
This research was a quasi - experimental design. The purpose was to test the result of square - stepping exercise on confidence without fear while performing activities, balance and walking performance. The sample included 68 elderly adults divided into control and experimental groups. Each group consisted of 34 samples. The experimental group performed square-stepping exercise 50 minutes at a time, 3 times a week for 8weeks. The control group did not perform square - stepping exercise. The instruments used to collect data were the recording form of personal data, the questionnaire to evaluate elderly’ confidence while performing activities without fear of fall, the recording form of the Time Up and Go Test, and the walking performance assessment form. The analysis was descriptive statistics and independent sample t-test. The findings revealed that the elderly who performed square-stepping exercise had confidence performing activities, without fear better balance and walking performance significance higher than before the experiment at the significance level of .05. In addition, the elderly who performed square-stepping exercise had higher confidence while performing activities without fear, and walking performance than those of the control group at the significance level of .05. However, the balance was not significantly different.